2019
DOI: 10.3389/fneur.2019.01020
|View full text |Cite
|
Sign up to set email alerts
|

Small Vessel Disease

Abstract: Small vessel disease (SVD) refers to conditions where damage to arterioles and capillaries is predominant, leading to reduced, or interrupted perfusion of the affected organ. Data suggest that when this condition is evident in any organ, it is already systemic in its occurrence and consequences. SVD affects primarily organs that receive significant portions of cardiac output such as the brain, the kidney, and the retina. Thus, SVD is a major etiologic cause in debilitating conditions such as renal failure, bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 83 publications
1
37
1
1
Order By: Relevance
“…Reduced CBF is correlated with accelerated cognitive decline and ultimately leads to dementia (Hakim, 2019). Using MRI analyses and clinical history data for 59 patients who suffered a transient ischemic attack, Wang and colleagues reported that 67.8% of such patients presented a history of hypertension.…”
Section: Hypoperfusion and Oxidative Stress In Hypertensionmentioning
confidence: 99%
“…Reduced CBF is correlated with accelerated cognitive decline and ultimately leads to dementia (Hakim, 2019). Using MRI analyses and clinical history data for 59 patients who suffered a transient ischemic attack, Wang and colleagues reported that 67.8% of such patients presented a history of hypertension.…”
Section: Hypoperfusion and Oxidative Stress In Hypertensionmentioning
confidence: 99%
“…While exciting new developments are in the pipeline, several lines of investigation indicate a significant impact lifestyle has on vascular health ( Hakim, 2014 , 2019 ) and particularly on brain angiogenesis and stroke outcome ( Schmidt et al, 2013 ). A short interval of exercise prior to stroke was shown to improve functional outcomes by enhancing angiogenesis ( Pianta et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The condition may lead to alteration of microcirculation (i.e., blood flow or perfusion) of the affected organ. SVD is generally observed in major organs such as the brain, retinal, heart, and urinary system (i.e., kidney), due to fact that these organs primarily required a desirable amount of cardiac output for their functionality (27). However, the GIT arteries are rarely affected to vascular disease either SVD or large vessel disease (i.e., atherosclerosis) (28).…”
Section: Small Vessel Disease-an Overviewmentioning
confidence: 99%
“…Interestingly, recent evidence suggested that higher SVD incidence is associated with an increased systemic inflammation due to poor sleep quality (39), as well as societal-based depression and loneliness (40)(41)(42). Besides, individual(s) with SVD is suggested to suffer from "systemic" condition (27). This is so as SVD is commonly associated with nervous system disturbances such as stroke, cognitive decline, vascular dementia, and gait dysfunction (43)(44)(45)(46).…”
Section: Risk Factors and Clinical Relevance Of Svdmentioning
confidence: 99%